Competency-based secondary teacher education program in Ethiopia: Potential opportunities and obstacles - Reda Darge Negasi (College of education, Bahir Dar University, 2023)
Prompted by increased concern about the competence model for teacher- preparation in Ethiopia, this article discussed the then pre-service Secondary Teacher Education Program that makes visible four different components which are required for competence - to outline the level of achievement that the prospective secondary School teachers must reach to fit the Graduate Teacher profiles. The article explored that government's influence through the auspices of the Teacher Education System Overhaul (TESO) may lead to a race for standards in which competence statements are employed as an important quality control for aspiring teachers who fit the Graduate Teacher Profiles. However, the article subsequently cautioned that those involved in producing effective teachers should take care in structuring secondary Teacher Education Program that is based on the premise that a competence approach to development and assessing is trouble free. The article further explored the assumption that effective teaching can be ensured simply by isolating particular skills for training, structuring them in a hierarchy that reflects the way that student teachers progress in their ability to teach, and then assessing them using the same schedule of competence statements, must be considered in light of the value-laden nature of teaching. The assumption that competence can be reduced to simple "ticking off" a list of competencies does not confirm that a student is an effective teacher for there are the many influences of contextual factors attending the task of teaching and interpreting its effectiveness. Finally, in drawing a conclusion, the article suggested that in aligning their program with the competence statements contained within the national curriculum, Teacher Education Institutions must not neglect the developmental aspect of the skills that enable student teachers to reach the Graduate Teacher Profiles. Every Teacher Education Institution has to make decisions about the best way to incorporate the statements into their program and assessment of practical teaching.